HUBUNGAN ANTARA IMT (INDEKS MASSA TUBUH) DENGAN KEJADIAN DISMENOREA PADA REMAJA PUTRI KELAS VII DI SMPN 1 MOJOANYAR - Frilasari, Heni (JURNAL KEPERAWATAN BINA SEHAT, 2015)
Dysmenorrhoea is pain before, during, and after menstruation. This disorderusually begins tooccurat 24 hoursbefore the onset ofmenstrual bleeding and can befelt 24-36 hours. Dysmenorrhoeais influenced by several factors, among others, psychological factors, constitutional factors, cervical canal obstruction factors, endocrine factors, allergic factors, andstatus of thebody mass indexof less/low. The purpose of this study was relationship between BMI (Body Mass Index) with the incidence of dysmenorrhoea to adolescent girls in class VII SMPN 1 Mojoanyar Mojokerto regency. The design of this study was analytical cross-sectional correlational approach. The population was the entire classVII student at SMPN 1 Mojoanyar much as 132 and the sample was 56 respondents drawn using cluster sampling technique. Data was obtained by questionnaire respondents whish it spreaded and measured height and weight to determine BMI of respondents. Processing data was done by editing, coding, scoring and tabulation. The result of this study was chi square test. And it showed was ρ=0.19, α=0.05. Then ρ>α, then H0 was rejected, the meaning a relationship between BMI (body massindex) with the incidence of dysmenorrhoea to adolescent girls in class VII SMPN 1 Mojoanyar. This situation occurs due to the factors influence the incidence of dysmenorrhoea among other nutritional status. Respondent should be more attention to the nutritional status of its normal BMI and can minimize the incidence of dysmenorrhoea.Keywords: BMI (Body Mass Index), Dysmenorrhoea, Teenagers